Teacher’s Efforts in Instilling Student Religious Character Education Through the Habitutation Method - Lestari, Sri; Minsih (Universitas Pendidikan Ganesha, 2023)
Teachers play a crucial role in developing students' character in the classroom, which is why character education is a priority. In order for our nation's values, customs, and identity to flourish, character education must be shaped. There should be mandatory character education classes for kids of all ages. This study aims to analyze teachers' efforts to instill religious character in students using the inductive method. Case study methodology and observation, interviews, and documentation are employed to obtain data for this qualitative study. Participants included the school principal and six teachers from grades 1-6. Data collection, data reduction, data display, and conclusion drawing are the four steps that make up interactive data analysis methodologies. This study concludes that the use of the habituation method to teach pupils about religion is highly effective, and that students benefit greatly from this approach. The findings of this study have important implications for the classroom, suggesting that teachers routinely employ habituation techniques that are proven to increase students' religious character without resorting to pressure.